MANAGEMENT OF ORAL HEALTH CHALLENGES IN PREGNANT WOMEN - Mihaela Mitrea; Razvan Radu Maxim; Allia Dmour; Irina Jemnoschi Hreniuc; Marius Constantin Moraru; Simona Alice Partene Vicoleanu; Ovidiu Mihail Stefanescu; Oana Elena Ciurcanu; Irina Luciana Gurzu; Vlad Danila; Irina Lavinia Stoian; Catalin Mihai Buzduga; et al. (Romanian Society of Oral Rehabilitation, 2022)
Pregnancy is a dynamic state leading to several physiological transient changes in the body system including the oral cavity. In order to maintain good oral health, the dental treatment should not be avoided. The dental management of pregnant patients involves special consideration as otherwise a hypersensitive vomit reaction in the third trimester of pregnancy can influence the eating behavior of the patient as well as oral hygiene influencing the appearance of dental erosion and tooth decay. Once pregnant women suffer an unpleasant gag reflex in a dental office, they may become phobic, delaying or postponing their dental treatment. The dental management of pregnant patients involves special considerations.